2016
DOI: 10.18632/oncotarget.13833
|View full text |Cite
|
Sign up to set email alerts
|

The pre-existing population of 5S rRNA effects p53 stabilization during ribosome biogenesis inhibition

Abstract: Pre-ribosomal complex RPL5/RPL11/5S rRNA (5S RNP) is considered the central MDM2 inhibitory complex that control p53 stabilization during ribosome biogenesis inhibition. Despite its role is well defined, the dynamic of 5S RNP assembly still requires further characterization. In the present work, we report that MDM2 inhibition is dependent by a pre-existing population of 5S rRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…WRS fibroblasts have a clear increase in pP53 expression as compared to control fibroblasts, suggesting a potential pathway of POLR3-mediated P53 regulation that is lost upon POLR3A mutation. As mentioned, the regulation of P53 is mediated in part by 5S rRNA, which is a specific POLR3 target gen (Onofrillo et al, 2017). WRS cells have a high increase of H2AX activity.…”
Section: Discussionmentioning
confidence: 93%
“…WRS fibroblasts have a clear increase in pP53 expression as compared to control fibroblasts, suggesting a potential pathway of POLR3-mediated P53 regulation that is lost upon POLR3A mutation. As mentioned, the regulation of P53 is mediated in part by 5S rRNA, which is a specific POLR3 target gen (Onofrillo et al, 2017). WRS cells have a high increase of H2AX activity.…”
Section: Discussionmentioning
confidence: 93%
“…Besides MDM4, the MDM2 protein is also a target of stress signaling, and this is already known to include nucleolar stress. Not only the 5S RNP, including the ribosomal proteins L5 and L11, binds to MDM2 and prevents p53 ubiquitination (Donati et al, 2013; Onofrillo et al, 2017); other nucleolar proteins, such as nucleophosmin and perhaps even p14 ARF , move from nucleoli to nucleoplasm upon nucleolar stress, where they bind and antagonize MDM2 (Kurki et al, 2004; Llanos et al, 2001; Sherr, 2006; Yang et al, 2016). Besides the 5S RNP, additional ribosomal proteins were found in association with MDM2, including L22 (Cao et al, 2017; Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…uL18 and uL5 have a crucial role in the p53-dependent nucleolar stress signaling pathway, which is activated in conditions of altered ribosome biogenesis [ 28 ]. In particular, it has been demonstrated that uL18 and uL5 regulate p53 homeostasis and its activation together with 5S rRNA as part of a ribosomal subcomplex—the 5S ribonucleoprotein particle (5S RNP) [ 29 , 30 ]. Specifically, in stressed cells, uL5 translocates into the nucleoplasm and associated with the pre-existing 5S/uL18 complex to form 5S RNP that binds to MDM2, thus regulating p53 levels [ 31 ].…”
Section: Role Of Ribosome Biogenesis In Neoplastic Transformationmentioning
confidence: 99%